Seafloor constraints on the reconstruction of Gondwanaland - Veevers, J. J.; Powell, C. McA; Johnson, B. D. (Earth and Planetary Science Letters, 1980)
M-series magnetic anomalies in the Mozambique Basin, off Dronning Maud Laud, and off the western margin of Australia, taken with other oceanic evidence, are used to test a new fit of Gondwanaland in which Madagascar adjoins the northern part of the western margin of India, the Falkland Plateau opposes part of Antarctica, and the southern part of South America fits without deformation into the Weddell Sea re-entrant of Antarctica. The first stage of spreading, from 150 m.y. to 125 m.y., is between East and West Gondwanaland, during which Madagascar, as part of East Gondwanaland, rotated half-way to its present position. The second stage, from 125 m.y. to 105 m.y., began with the separation of South America from Africa, and Antarctica-Australia from India-Madagascar, and ended with Madagascar reaching its final position with respect to Africa. In the third stage, from 105 m.y. to just before 90 m.y., spreading continued except between India-Madagascar and Africa which were part of a single plate. A major reorganisation of spreading systems at the end of the third stage saw India separate from Madagascar. In our reconstructions, a slight mismatch between the modelled transform faults and the observed fracture zone on the eastern side of the Dronning Maud set suggests that only small adjustments are required to the new reconstruction of Gondwanaland.